Reactive Oxygen Species and Tumor Metastasis - Lee, Doo Jae (Korea Society for Molecular and Cellular Biology, 2013)
The migration and invasion of cancer cells are the first steps in metastasis. Through a series of cellular responses, including cytoskeletal reorganization and degradation of the extracellular matrix, cancer cells are able to separate from the primary tumor and metastasize to distant locations in the body. In cancer cells, reactive oxygen species (ROS) play important roles in the migration and invasion of cells. Stimulation of cell surface receptors with growth factors and integrin assembly generates ROS, which relay signals from the cell surface to important signaling proteins. ROS then act within cells to promote migration and invasion. In this review, we collect recent evidence pointing towards the involvement of ROS in tumor metastasis and discuss the roles of ROS at different stages during the process of cancer cell migration, invasion and epithelial-mesenchymal transition.